ANALISIS KARAKTER MIKROSTRUKTUR PERMUKAAN DAN TENSILE SS304 PADA PENGELASAN SMAW DENGAN ARUS 85 AMPERE: ANALYSIS OF MICROSTRUCTURE AND TENSILE PROPERTIES OF SS304 UNDER SMAW WELDING AT 85 AMPERE - Hanif Ridhwanul Majid; Moch Wisnu Arif Sektiono,S.Si., M.Si.; Setiyo Rojikin, S.T., M.T. (Mechanical Engineering Department Polinema Kediri, 2026)
This study aims to analyze the crystal structure changes on Stainless Steel 304 (SS304) metal surface welded using Shielded Metal Arc Welding (SMAW) method at 85 Ampere current. SS304 material with specific thickness was welded using Nikko Steel NSN-308 electrode with 2.6 mm diameter. Tensile test specimens were prepared according to ASTM E8 standard with single V groove joint design (60° angle, 2 mm gap). Tensile testing results showed average Ultimate Tensile Strength (UTS) of 589.35 MPa, and Yield Strength (YS) of 354.48 MPa. Metallographic analysis using optical microscope identified three distinct zones: base metal with uniform polygonal δ-ferrite and γ-austenitee grain structure, Heat Affected Zone (HAZ) with grain enlargement and partial recrystallization, and weld metal with dendritic structure due to cooling. process. The research results indicate that SMAW welding process at 85 Ampere causes significant microstructural changes, where γ-austenitee crystal structure stability and grain size and shape variations become the main factors affecting material mechanical properties.